Viewpoint: Developing Modules on the Topic of Education for Sustainable Development- A Cross-cultural Approach for Engaging in International Collaboration and Furikaeri - Jon Clark; Andrew Petersen; Kazuo Kitahara; Masafumi Nagao; Yutaka Sato (Environmental Association of Southern Africa, 2009)
The aim of the project reported on in this viewpoint paper is to develop a package of curriculum materials for use in the teaching of the topic of Education for Sustainable Development (ESD) at the primary school level. The project is an international collaboration between teachers in primary schools in Cape Town (South Africa) and Toyko (Japan), supported by researchers at two Universities - The International Christian University (ICU) in Toyko and The University of Cape Town (UCT). The curriculum materials are being developed jointly by teachers in the two countries, through a collaborative process that involves a number of reciprocal visits to each others' classrooms and participation in video conferences together. Once completed, the materials will be trialed in the respective contexts. A further feature of the project is the use of the Japanese system of Furikaeri (or 'lesson study'). This is a form of reflective practice which has been shown to be a most useful tool in support of teacher professional development